2020
DOI: 10.1038/s41370-020-00279-0
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and endocrine disrupting chemical-associated personal care product use among US-based foreign-born Chinese women of reproductive age

Abstract: Background: Personal care products (PCPs) are an important source of endocrine disrupting chemicals (EDCs) linked to adverse reproductive health outcomes. Objective: We evaluated EDC-associated PCP use and acculturation among Asian women. Methods: Our study included 227 foreign-born Chinese women ages 18–45 seeking obstetrics-gynecology care at community health centers (Boston, MA). Acculturation was measured by English-language use, length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Further, even within certain categories, there are differences in experiences that may influence products use; for example, acculturation has been associated with increased product use among foreign-born Chinese women (38). The US multiracial population is also growing and in 2000, the US Census added the option for the first time to check more than one race.…”
Section: Categorizing Race and Ethnicitymentioning
confidence: 99%
“…Further, even within certain categories, there are differences in experiences that may influence products use; for example, acculturation has been associated with increased product use among foreign-born Chinese women (38). The US multiracial population is also growing and in 2000, the US Census added the option for the first time to check more than one race.…”
Section: Categorizing Race and Ethnicitymentioning
confidence: 99%
“…Occupational exposures to chemicals in nail salon products have been studied in Vietnamese women [21,22], but assessment of personal product use is very limited. One study of Chinese women found that a higher level of acculturation in the U.S. was associated with higher use of several types of personal care products [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some Asian women, particularly Vietnamese women, have higher than average exposures to nail salon products due to their occupation [35], but there is little information about their own personal use of cosmetics and other products. One published study showed that a higher level of acculturation of Chinese women in Boston was associated with higher use of personal care products, but they only examined nine products [36]. Use of skin lightening creams is prevalent in both Asian and Latina women [37,38], and there have been documented cases of people exposed to mercury through skin lightening cream imported from Mexico [38].…”
Section: Introductionmentioning
confidence: 99%